2007
DOI: 10.1182/blood-2007-06-096651
|View full text |Cite
|
Sign up to set email alerts
|

The ligand occupancy of endothelial protein C receptor switches the protease-activated receptor 1-dependent signaling specificity of thrombin from a permeability-enhancing to a barrier-protective response in endothelial cells

Abstract: Recent studies have indicated that activated protein C (APC) may exert its cytoprotective and anti-inflammatory activities through the endothelial protein C receptor (EPCR)-dependent cleavage of protease-activated receptor 1 (PAR-1) on vascular endothelial cells. Noting that (1) the activation of protein C on endothelial cells requires thrombin, (2) relative to APC, thrombin cleaves PAR-1 with approximately 3 to 4 orders of magnitude higher catalytic efficiency, and (3) PAR-1 is a target for the proinflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
372
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 210 publications
(393 citation statements)
references
References 39 publications
19
372
2
Order By: Relevance
“…These observations are dependent on APC binding to its specific receptor, endothelial protein C receptor (EPCR), although this receptor does not signal. The proposed mechanism involves APC binding to EPCR, activating PAR-1, and transactivating the epidermal growth factor receptor (46,50,51). Cleavage of PAR-1 by APC bound to EPCR within a lipid raft activates Gi and subsequent antiinflammatory signals.…”
Section: Activated Protein C (Apc)mentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are dependent on APC binding to its specific receptor, endothelial protein C receptor (EPCR), although this receptor does not signal. The proposed mechanism involves APC binding to EPCR, activating PAR-1, and transactivating the epidermal growth factor receptor (46,50,51). Cleavage of PAR-1 by APC bound to EPCR within a lipid raft activates Gi and subsequent antiinflammatory signals.…”
Section: Activated Protein C (Apc)mentioning
confidence: 99%
“…Cleavage of PAR-1 by APC bound to EPCR within a lipid raft activates Gi and subsequent antiinflammatory signals. When PAR-1 is activated outside the lipid raft by other serine proteinases, signaling via Gq and/or G12/13 occurs, leading to proinflammatory signals (50).…”
Section: Activated Protein C (Apc)mentioning
confidence: 99%
“…EPCR-FVIIa complexes neither activate FX (31) nor induce cell signaling through activation of PAR1 or PAR2 (31,36). FVIIa binding to EPCR has no influence on the formation of TF-FVIIa complexes on activated endothelial cells (31).…”
Section: Fviia Association With Epcr On Endotheliummentioning
confidence: 99%
“…Recent studies of Bae et al [18] also suggested that FVIIa binding to EPCR does not induce cell signaling since FVIIa failed to prevent enhanced cell permeability induced by thrombin. However, these studies alone do not completely rule out a role for EPCR-FVIIa in cell signaling.…”
Section: Cellular Consequences Of Fviia Binding To Epcrmentioning
confidence: 99%